From Lab to Life: Self‐Powered Sweat Sensors and Their Future in Personal Health Monitoring - Nan Gao; Guodong Xu; Gang Chang; Yuxiang Wu (Advanced Science)
Abstract The rapid development of wearable sweat sensors has demonstrated their potential for continuous, non‐invasive disease diagnosis and health monitoring. Emerging energy harvesters capable of converting various environmental energy sources—biomechanical, thermal, biochemical, and solar—into electrical energy are revolutionizing power solutions for wearable devices. Based on self‐powered technology, the integration of the energy harvesters with wearable sweat sensors can drive the device for biosensing, signal processing, and data transmission. As a result, self‐powered sweat sensors are able to operate continuously without external power or charging, greatly facilitating the development of wearable electronics and personalized healthcare. This review focuses on the recent advances in self‐powered sweat sensors for personalized healthcare, covering sweat sensors, energy harvesters, energy management, and applications. The review begins with the foundations of wearable sweat sensors, providing an overview of their detection methods, materials, and wearable devices. Then, the working mechanism, structure, and a characteristic of different types of energy harvesters are discussed. The features and challenges of different energy harvesters in energy supply and energy management of sweat sensors are emphasized. The review concludes with a look at the future prospects of self‐powered sweat sensors, outlining the trajectory of the field and its potential to flourish.